(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article is devoted to the expression of the economizing phenomena in the syntactic stage. The purpose of the study is to analyze the nature of economizing of the language tools. In incomplete sentences and dialogues, the manifestations of the phenomenon of economizing, the reasons for its emergence were studied on the basis of artistic text materials. In particular, the article proves that dialogues are a real manifestation of the economizing.